Expression and Functional Evaluation of Recombinant Anti-receptor Activator of Nuclear Factor Kappa-B Ligand Monoclonal Antibody Produced in Nicotiana benthamiana - Boonyayothin, Wanuttha; Sinnung, Sirorut; Shanmugaraj, Balamurugan; Abe, Yoshito; Strasser, Richard; Pavasant, Prasit; Phoolcharoen, Waranyoo (Frontiers in Plant Science, 2021)
Denosumab, an anti-receptor activator of nuclear factor-kappa B ligand antibody (anti-RANKL), is a fully human monoclonal antibody (mAb) available for the treatment of osteoporosis. In the present study, an anti-RANKL mAb was transiently expressed using the geminiviral expression system in Nicotiana benthamiana, and the functional activity of the plant-produced mAb was determined. The highest expression level of the plant-produced mAb was found at 8 days post-infiltration, and it was estimated to be 0.5 mg/g leaf fresh weight. The recombinant mAb from the plant crude extracts was purified by using Protein A affinity column chromatography. The plant-produced mAb demonstrated good in vitro affinity binding with human RANKL, as determined by RANKL-ELISA binding. The function of the plant-produced mAb was evaluated in vitro. CD14-positive cells isolated from human peripheral blood mononuclear cells (PBMCs) were cultured in vitro in the presence of human RANKL and macrophage-colony-stimulating factor (M-CSF) to stimulate osteoclastogenesis. The results demonstrated that plant-produced mAb could significantly decrease the number of osteoclasts compared to commercial denosumab. These results demonstrated that the plant-produced mAb has the potential to inhibit osteoclast differentiation and that it could be considered for osteoporosis treatment.